Preparation of the Endometrium for Frozen Embryo Transfer: A Systematic Review - Mumusoglu, Sezcan; Polat, Mehtap; Ozbek, Irem Yarali; Bozdag, Gurkan; Papanikolaou, Evangelos G.; Esteves, Sandro C.; Humaidan, Peter; Yarali, Hakan (Frontiers in Endocrinology, 2021)
Despite the worldwide increase in frozen embryo transfer, the search for the best protocol to prime endometrium continues. Well-designed trials comparing various frozen embryo transfer protocols in terms of live birth rates, maternal, obstetric and neonatal outcome are urgently required. Currently, low-quality evidence indicates that, natural cycle, either true natural cycle or modified natural cycle, is superior to hormone replacement treatment protocol. Regarding warmed blastocyst transfer and frozen embryo transfer timing, the evidence suggests the 6th day of progesterone start, LH surge+6 day and hCG+7 day in hormone replacement treatment, true natural cycle and modified natural cycle protocols, respectively. Time corrections, due to inter-personal differences in the window of implantation or day of vitrification (day 5 or 6), should be explored further. Recently available evidence clearly indicates that, in hormone replacement treatment and natural cycles, there might be marked inter-personal variation in serum progesterone levels with an impact on reproductive outcomes, despite the use of the same dose and route of progesterone administration. The place of progesterone rescue protocols in patients with low serum progesterone levels one day prior to warmed blastocyst transfer in hormone replacement treatment and natural cycles is likely to be intensively explored in near future.